From goodness to good looks: Changing images of human germline genetic modification. (3rd July 2021) - So, Derek
Abstract: When writing about deliberate changes to the human germline, bioethicists tend not to discuss the modification of specific genes and instead refer to broader concepts like making people smarter, taller, or longer‐lived. Only a limited number of these traits are mentioned regularly in the literature. Examples like health and intelligence appear frequently at all stages of the germline modification discourse, but the third most frequently mentioned trait has shifted over time. Prior to the early 1980s, publications discussed giving humans a kinder temperament significantly more often than cosmetic modifications, while more recent works reverse the frequency of these traits. Contributing factors likely include a greater focus on individual decision‐making, combined with the increasing uptake of real‐world reproductive technologies like IVF and gamete donation. This shifting imagery could have a profound influence on the way scholars develop arguments about gene editing since cosmetic modifications are generally viewed more negatively and considered less relevant to the identity of future people. In comparison with earlier images of germline modification, they also suggest a more contemporary, Western, and politically liberal social context for gene editing technology. Examining how authors move between writing about different traits can also help us to be aware of the traits that are arbitrarily omitted from the discourse and to consider our preparedness for unexpected kinds of modification.